Perbandingan Alat Transportasi Tandan Buah Segar (TBS) antara Dump truck dan Truk Bak Kayu pada Masa Tanaman Menghasilkan - Dzikri Aziz Ramadhan; Jojon Soesatrijo; Toto Suryanto (JURNAL CITRA WIDYA EDUKASI, 2019)
This study discusses the comparison of transportation of fresh fruit bunches (FFB) between dump truck and ordinary truck during the time the plants are produced, conducted at PT Sinar Dinamika Kapuas, Sintang District, West Kalimantan Province, since April 2015. The purpose of this study is to find out the advantage and disadvantage of dump truck and ordinary truck, and to compare them as a mean of transporting FFB on palm oil plantation. This study used 10 trucks as samples, consisting of 5 dump trucks and 5 ordinary trucks. Data gathering was taken from the FFB daily daily report data for the April 2015 period. The result of this study showed that dump truck transported an average of 8,438 kg FFB/rit and ordinary truck of 9,139 kg FFB/rit. The income of the dump truck is Rp 13,046,196 and the ordinary truck is Rp 14,161,532. The income from the dump truck is Rp 821,695 to PT SDK, Rp 706,388 to PT BPJ and Rp 805,147 to PT KSP. The revenue from the ordinary truck sent Rp 857,335 to PT SDK, Rp 749,038 to PT BPJ and Rp 860,415 to PT KSP. The difference in income sent Rp 35,640 to PT SDK, Rp 42,650 to PT BPJ and Rp 55,286 to PT KSP. The difference occurs when loading in the loading ramp because the ordinary truck cost Rp 50,000/rit.